Znaczenie etyki we współczesnych przedsiębiorstwach - Teneta-Skwiercz, Dorota (The significance of ethics in contemporary companies, 2006)
This article takes part in the discussion about ethics in companies. In the introduction some concepts of ethics are defined, among which the most important are: ethics of business, ethics in general and ethics in business. It is a basis to characterise the basic attributes of “moral culture” of the company. The paper also discusses some instruments of making ethics more institutionalised in managing, and then introducing ethics into management.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (4); 2006; nr 1114, s. 42-48